2015 IEEE 21st International Symposium on High Performance Computer Architecture (HPCA) 2015
DOI: 10.1109/hpca.2015.7056070
|View full text |Cite
|
Sign up to set email alerts
|

Malware-aware processors: A framework for efficient online malware detection

Abstract: Security exploits and ensuant malware pose an increasing challenge to computing systems as the variety and complexity of attacks continue to increase. In response, software-based malware detection tools have grown in complexity, thus making it computationally difficult to use them to protect systems in real-time. Therefore, software detectors are applied selectively and at a low frequency, creating opportunities for malware to remain undetected. In this paper, we propose Malware-Aware Processors (MAP) -process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(55 citation statements)
references
References 42 publications
(48 reference statements)
1
47
0
Order By: Relevance
“…This dataset is sufficiently large to establish the feasibility and provide a reasonable evaluation of the proposed approach. The features were collected once every 10,000 committed instructions of the program, consistent with the methodology used by earlier works that use this approach [6,23]. These prior studies demonstrated that classification at this frequency effectively balances complexity and detection accuracy for offline [6] and online [23] detection.…”
Section: Programs Used For This Studymentioning
confidence: 99%
See 4 more Smart Citations
“…This dataset is sufficiently large to establish the feasibility and provide a reasonable evaluation of the proposed approach. The features were collected once every 10,000 committed instructions of the program, consistent with the methodology used by earlier works that use this approach [6,23]. These prior studies demonstrated that classification at this frequency effectively balances complexity and detection accuracy for offline [6] and online [23] detection.…”
Section: Programs Used For This Studymentioning
confidence: 99%
“…The features were collected once every 10,000 committed instructions of the program, consistent with the methodology used by earlier works that use this approach [6,23]. These prior studies demonstrated that classification at this frequency effectively balances complexity and detection accuracy for offline [6] and online [23] detection. For each program we maintained a sequence of these feature vectors collected every 10K instructions, labeled as either malware or normal.…”
Section: Programs Used For This Studymentioning
confidence: 99%
See 3 more Smart Citations